A single bout of exercise with a flexible pole induces significant cardiac autonomic responses in healthy men - Ogata, Cristiane M. [UNESP] (2014)
OBJECTIVES: Flexible poles can provide rapid eccentric and concentric muscle contractions. Muscle vibration is associated with a "tonic vibration reflex" that is stimulated by a sequence of rapid muscle stretching, activation of the muscle spindles and stimulation of a response that is similar to the myotatic reflex. Literature studies analyzing the acute cardiovascular responses to different exercises performed with this instrument are lacking. We investigated the acute effects of exercise with flexible poles on the heart period in healthy men.METHOD: The study was performed on ten young adult males between 18 and 25 years old. We evaluated the heart rate variability in the time and frequency domains. The subjects remained at rest for 10 min. After the rest period, the volunteers performed the exercises with the flexible poles. Immediately after the exercise protocol, the volunteers remained seated at rest for 30 min and their heart rate variability was analyzed.RESULTS: The pNN50 was reduced at 5-10 and 15-20 min after exercise compared to 25-30 min after exercise (p = 0.0019), the SDNN was increased at 25-30 min after exercise compared to at rest and 0-10 min after exercise (p = 0.0073) and the RMSSD was increased at 25-30 min after exercise compared to 5-15 min after exercise (p = 0.0043). The LF in absolute units was increased at 25-30 min after exercise compared to 5-20 min after exercise (p = 0.0184).CONCLUSION: A single bout of exercise with a flexible pole reduced the heart rate variability and parasympathetic recovery was observed approximately 30 min after exercise.